A Convenient Synthesis of Functionalized Azulenes via Negishi Cross-Coupling - Dubovik, Julia; Bredihhin, Aleksei (Synthesis, 2015)
A mild and effective method for the synthesis of functionalized azulenes is described. Negishi cross-coupling of bromoazulenes with functionalized aromatic, heterocyclic, benzylic, and alkylic organozinc reagents affords substituted azulenes in good yields. Functional groups, including ethoxycarbonyl, cyano, methoxy, fluoro, chloro, and bromo are well tolerated. Additionally, a one-pot procedure for introducing two different substituents into positions 1 and 3 of azulene through cross-coupling reaction is described for the first time.
Keywords: azulene; cross-coupling; halogenation; heterocycles; organometallic reagents